Association between Fragmentation and Various Substitution Features: A Study on Isoflavonoids Analogues by CID and HCD Using LTQ Orbitrap Mass Spectrometry - Yang, Min; Zhou, Zhe; Qv, Hua; Jiang, Baohong; Liu, Xuan; Wu, Wanying; Guo, De-an (Current Traditional Medicine, 2015)
Isoflavonoids were rich in natural source and gained great attention due to their diverse activities such as antioxidant, estrogenic, radical scavenging and prevention of cardiovascular and coronary heart diseases. Numerous isoflavonoids, usually present as isomers, were found in traditional medicines and dietary supplements. For better understanding of the unknown components, thorough investigation on the known analogue compounds was essential and helpful. In the present study, a new developed fourier transform mass spectrometry (FTMS), named Orbitrap, which applied as a hybrid instrument with one type of linear ion trap (LTQ), was used. Collision induced dissociation (CID) and higher collision energy dissociation (HCD) were applied in both negative and positive ion modes. Association between fragmentation patterns and different substitution modes were clarified. In most cases, the key differences just lie in distinct abundance of the fragment ions. Therefore, comparative studies on series of spectra profiles were more useful than simple consideration of the fragmentation pathways sometimes. General fragmentation rules of isoflavonoinds and distinctive characteristic of some isomers were summarized by combined use of CID and HCD methods. The obtained results would be valuable for structural characterization of analogues in isoflavone rich traditional medicines and dietary supplements.
Keywords: fragmentation library